5(x+3)(2x-7)=

Simple and best practice solution for 5(x+3)(2x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)(2x-7)= equation:


Simplifying
5(x + 3)(2x + -7) = 0

Reorder the terms:
5(3 + x)(2x + -7) = 0

Reorder the terms:
5(3 + x)(-7 + 2x) = 0

Multiply (3 + x) * (-7 + 2x)
5(3(-7 + 2x) + x(-7 + 2x)) = 0
5((-7 * 3 + 2x * 3) + x(-7 + 2x)) = 0
5((-21 + 6x) + x(-7 + 2x)) = 0
5(-21 + 6x + (-7 * x + 2x * x)) = 0
5(-21 + 6x + (-7x + 2x2)) = 0

Combine like terms: 6x + -7x = -1x
5(-21 + -1x + 2x2) = 0
(-21 * 5 + -1x * 5 + 2x2 * 5) = 0
(-105 + -5x + 10x2) = 0

Solving
-105 + -5x + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '5'.
5(-21 + -1x + 2x2) = 0

Factor a trinomial.
5((-3 + -1x)(7 + -2x)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(7 + -2x)' equal to zero and attempt to solve: Simplifying 7 + -2x = 0 Solving 7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5

Solution

x = {-3, 3.5}

See similar equations:

| 2+12h=-4h+2 | | -5r-22=-19-8r | | 12y-3-14y=-11 | | -1.5+1.2p=-3.9 | | 7x-4x+5=18 | | -1.5+12p=-3.9 | | 56x+3=58x-1 | | a=0.41+2b | | 6xy/9yz | | v(2v+3)-6(v-1)= | | -2(7.5+0.5y)+y=-15 | | -2(25.5+0.5y)+y=-51 | | 3=3+6v | | 4(3b-4)= | | -2x+y=-51 | | ya+xb=c | | 8x-13=23 | | 1a+-2b=.41 | | 56x+3+58x-1=180 | | x^3-18x^2+108x-256=0 | | (100/x)*x=(515/91)*x | | 40w+5(2w)=600 | | 0.2(x-30)=-1.6x | | (3x-6)(x-4)(x+6)=0 | | 24x-5+22x+5=180 | | 46x-5+5=180 | | 1000=(-1700)(10)+b | | 57/67×32/171×45/128 | | 5(x+3)-1(2x-7)= | | 13+4(x-5)=5-2x | | mx^2-(2m+1)x+(m-1)=0 | | 28x-2+110=180 |

Equations solver categories